Hermeneutika Khaleed M. Abou El-Fadl - Amin, Moh. Nasrul (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2019)
It cannot be denied that the problem of interpretation of religious texts often creates tension. Tensions often occur because each party, both community leaders, religious groups, organizations and fatwa institutions (such as the Permanent Council for specific Research and Legal Opinion (CRLO), Bahsul Masail, Majlis Tarjih, Hisbah Council, MUI Fatwa Commission), Mazhab, and certain religious schools. The fatwas according to Abou El-Fadl are said to be sheltered under the text (nash) which claims that it is actually "desired by God". According to him, the reinterpretation of Islamic legal interpretations is important to do so that Muslims are spared from the authoritarian interpreters in interpreting the text. Without realizing that they are trapped in the action of "interpretive authoritarianism". The phenomenon of this Absolute truth claim is much troubling and is seen as very problematic